2020
DOI: 10.3390/genes11111340
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizers Based on G-Quadruplex Ligand for Cancer Photodynamic Therapy

Abstract: G-quadruplex (G4) is the non-canonical secondary structure of DNA and RNA formed by guanine-rich sequences. G4-forming sequences are abundantly located in telomeric regions and in the promoter and untranslated regions (UTR) of cancer-related genes, such as RAS and MYC. Extensive research has suggested that G4 is a potential molecular target for cancer therapy. Here, we reviewed G4 ligands as photosensitizers for cancer photodynamic therapy (PDT), which is a minimally invasive therapeutic approach. The photosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 78 publications
1
17
0
1
Order By: Relevance
“…Indeed, contemporary research has demonstrated the importance of G4s in various cellular processes, including interactions with TFs [ 60 , 61 , 62 , 63 ]. Moreover, the targeting of the unique structure of G4s is proposed as a good tool for various diseases therapies including cancer [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, contemporary research has demonstrated the importance of G4s in various cellular processes, including interactions with TFs [ 60 , 61 , 62 , 63 ]. Moreover, the targeting of the unique structure of G4s is proposed as a good tool for various diseases therapies including cancer [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate that G-quadruplex prone sequences are abundant in human promoters [46,58]. Notably, the distinct abundance of G-prone sequences was detected in the promoters of oncogenes, suggesting the potential to use G-quadruplex regulation in cancer treatment [47,59]. Probably the best explored G-quadruplex in promoters is a sequence from the human c-Myc oncogene [60,61].…”
Section: Promoter Structure Motifsmentioning
confidence: 99%
“…Besides K + chelation, the material can also be be disassembled upon addition of a G4-binding porphyrin photosensitiser and exposure to longwave UV light (395-400 nm), the combination of which, as previously described, disrupts the quadruplex through guanine photo-oxidation. [35][36][37][38][39] This additional mechanism is irreversible but enables precise spatial control over the response. Owing to the combined assembly reversibility, multistimuli-responsiveness, and cargo-loading capabilities, we believe that Quad-Stars hold significant potential for applications such as smart biosensors and drug delivery carriers.…”
Section: Main Textmentioning
confidence: 99%